The Urgency of Regulating Articles of Association and Bylaws (AD/ART) in Ensuring Effective Cooperative Governance - Ana Fitrotun Nisa'; Imroatun Mufida; Dewi Lara Sati; Mashudi (Penerbit Hellow Pustaka, 2025)
The Articles of Association and Bylaws (AD/ART) play a central role in ensuring effective and sustainable governance within cooperatives. The Articles of Association serve as the normative framework of the organization, while the Bylaws provide the administrative foundation that governs technical operational implementation. This study aims to analyze the functions of AD/ART within the institutional structure of cooperatives and their contribution to the application of good governance principles such as transparency, accountability, responsibility, independence, and fairness. Using a qualitative-descriptive approach, this study explores the role of AD/ART in strengthening the legitimacy of cooperative organizations and in preventing internal conflicts and abuse of power. The findings indicate that well-structured AD/ART serve as a vital foundation in establishing cooperative governance that is democratic, professional, and accountable.